Trust Force And Hole Quality Observation In Various Major Penetration Angle Drilling Of Carbon Fibre Reinforced Plastic (CFRP) - Salleh, Mohd Shukor; Jaafar, Mohd Fairuz (Trans Stellar, 2020)
This paper has presented a new approach to study the comparison of thrust force and hole quality observation for three types of the drill with penetration angle of 0°, 15° and 30° for drilling carbon fibre reinforced plastic (CFRP) laminates. The experimental approach is adapting to a combination of the design of experiment Taguchi’s technique and analysis of variance (ANOVA). The drill types involved in the experiment are twist drill, dagger drill and straight flute drill. Plan of experiments adopted on the Taguchi technique with variable cutting parameters of drill types, drilling penetration angle, spindle speed and feed rate was performed in drilling autoclave carbon fibre reinforced plastic (CFRP) laminates. Based on the statistical experiment results, lower feed rate and lower penetration angle contribute lower thrust force at constant spindle speed operation for the twist, dagger and straight flute drill type based on response surface graph analysis in order of Taguchi design method. In term of hole quality observation, hole drilled with straight flute drill has the best hole quality compared with other drill types in this experiment. Drilling penetration angle contributes significant contribution to drilling thrust force and drilled hole quality.